Study on Giardia duodenalis and Cryptosporidium spp. infection in veterinarians in Poland - Angelina Wójcik-Fatla (Annals of Agricultural and Environmental Medicine, 2018)
The risk of exposure to zoonotic factors among veterinarians comprises still underestimated problem. Many etiological factors of infectious diseases are so far poorly known, including the way of their transmission from environment to humans and their impact for health. The main aim of the study was to determine the risk of two selected zoonosis infections caused by Giardia duodenalis and Cryptosporidium spp. among occupational group of veterinarians in Poland. Two hundred ninety seven samples of stool were tested for the presence of Giardia cysts and Cryptosporidium oocysts using Direct Fluorescent Assay (DFA). There were no positive results for Cryptosporidium . The presence of Giardia cysts was found in two samples of faeces (0.67%), confirmed by polymerase chain reaction and sequencing. The risk with regard to the parasites Giardia duodenalis and Cryptosporidium spp. seems to be low among the group of veterinarians.